If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + 6 = 4x + -50 Reorder the terms: 6 + -4x = 4x + -50 Reorder the terms: 6 + -4x = -50 + 4x Solving 6 + -4x = -50 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 6 + -4x + -4x = -50 + 4x + -4x Combine like terms: -4x + -4x = -8x 6 + -8x = -50 + 4x + -4x Combine like terms: 4x + -4x = 0 6 + -8x = -50 + 0 6 + -8x = -50 Add '-6' to each side of the equation. 6 + -6 + -8x = -50 + -6 Combine like terms: 6 + -6 = 0 0 + -8x = -50 + -6 -8x = -50 + -6 Combine like terms: -50 + -6 = -56 -8x = -56 Divide each side by '-8'. x = 7 Simplifying x = 7
| 9(x+2)-11=12+3x | | 2w-5+3(4w+1)=-2(w+8) | | (-9p)-17=10 | | .5x^2-180x+32188=c | | r/8=6 | | 2(3a+4b)(6a+7b)=0 | | 6y+7-3(-3y-1)=5(y-1) | | X^2-4x-46=0 | | 18x-5y=y+4 | | x(6x+13)=28 | | 4x^2-21x+16=-6x+7 | | 8(b-8)=32 | | 6(5w+5)=4(6w-7) | | 6x-4=5x+2 | | 16-(5m+7)=3+4m-12 | | 6(5+5)=4(6-7) | | 147+x=4x-36 | | x^2+12x-45=5x-1 | | 4.5*x=55.8 | | 12c+6-6c=40 | | -6.28q=18.84 | | 8x-7y=-35 | | 15n+n=7-12n | | 5.9t=-23.6 | | 36m^2-25n^2=0 | | 6(x+18)-18=3x+15 | | 7x+4=2x+59 | | 38-3x=8-9x | | 3(-h+5)=-6 | | 2a+2b=120 | | 15x+21=6x+246 | | m+0.4=0.6 |